TRIGONOMETRIC IDENTITIES PROBLEMS WITH SOLUTIONS

Trigonometric Identities Problems with Solutions :

Here we are going to see, some example problems to show proving trigonometric identities.

Trigonometric Identities Problems with Solutions - Questions

Question 1 :

(i) If (cos α/cos β) = m and (cos α/ sin β) = n then prove that (m2 + n2) cos2β  =  n2

Solution :

m  =  (cos α/cos β)

Taking squares on both sides

m2  =  (cos α/cos β)2

m2  =  (cosα/cosβ) ----------(1)

(cos α/ sin β) = n

n2  =  (cos α/sin β)2

n2  =  (cosα/sinβ) ----------(2)

(1) + (2)

m+ n2  =  (cosα/sinβ) + (cosα/cosβ)

  =  (cosα cosβ + cosα sinβ) / sinβ cosβ

  =  cosα (cosβ + sinβ) / sinβ cosβ

  =  cosα (1) / sinβ cosβ

 m+ n2   =  cosα / sinβ cosβ

(m+ n2⋅ cosβ  =  (cosα / sinβ cosβ)⋅ cosβ

  =  (cosα / sinβ)

  =  n2

(ii)  If cotθ + tan θ = x and sec θ −cos θ = y , then prove that (x2y)2/3 - (xy2)2/3  =  1

x = cotθ + tan θ

x = (cos θ/sin θ) + (sin θ/cos θ)

x = (cosθ + sinθ)/sin θ cos θ

x = 1/sin θ cos θ

x2 = 1/sin2 θ cosθ

y  =  sec θ −cos θ 

y  =  (1/cos θ) −cos θ 

y  =  (1 - cos2 θ)/cos θ

y  =  sin2 θ/cos θ

y2  =  sin4 θ/cosθ

x2y  =   (1/sin2 θ cosθ)  (sin2 θ/cos θ)

x2y  =   (1/cosθ)

(x2y)2/3  =   [(1/cosθ)]2/3

  =  1/cos2θ

 (x2y)2/3  =  sec2θ   ----(1)

(xy2)  =  (1/sin θ cos θ)(sin4 θ/cosθ)

  =  (sin3 θ/cosθ)

 (xy2)2/3  =  (sin2 θ/cosθ) 

 (xy2)2/3  = tan2θ ---(2)

(1) - (2)

(x2y)2/3 - (x2y)2/3  =  1

sec2θ - tan2θ  =  1

Hence proved.

Question 2 :

(i) If sin θ + cos θ = p and sec θ + cosec θ = q, then prove that q(p2 −1) = 2p

Solution :

p = sin θ + cos θ

p2 = (sin θ + cos θ)2

  =  sinθ + cosθ + 2 sin θ cos θ

p2  =  1 + 2 sin θ cos θ

p2 - 1  =  1 + 2 sin θ cos θ - 1

p- 1  =  sin θ cos θ

q = sec θ + cosec θ

q(p2 −1)  =  (sec θ + cosec θ)(sin θ cos θ)

  =  (1/cos θ) + (1/sin θ) (sin θ cos θ)

  =  [(sin θ cos θ)/cos θ] + [(sin θ cos θ)/sin θ]

  =  sin θ + cos θ

  =  2 (sin θ + cos θ)

  =  2 p

(ii)  If sin θ (1+ sin2 θ) = cos2 θ, then prove that cos6 θ    −4 cos4 θ + 8 cos2 θ = 4

Solution :

sin θ (1+ sin2 θ) = cos2 θ

sin θ + sin3 θ = 1 - sin2 θ

sin θ + sin2 θ + sin3 θ = 1 

sin θ + sin3 θ = 1 - sin2 θ 

taking squares on both sides,

(sin θ + sin3 θ) =  (1 - sin2 θ)

sin2θ + 2sin4θ + sin6θ  =  1 - 2sin2θ + sin4θ

sin2θ + 2sin2θ + 2sin4θ - sin4θ + sin6θ  =  1 

3sin2θ + sin4θ + sin6θ  =  1 

3(1 - cos2θ) + (1 - cos2θ)2 (1 - cos2θ)3  =  1 

3 - 3cos2θ + 1 + cos4θ - 2cos2θ + 1 - 3cos2θ + 3cos4θ - cos6θ  =  

4 - cos6θ + 4cos4θ - 8cos2θ  =  0

 cos6 θ − 4 cos4 θ + 8 cos2 θ = 4

Hence proved.

Question 3 :

If cos θ / (1 + sin θ) = 1/a, then prove that (a2 - 1)/(a2 + 1) = sin θ  

Solution :

cos θ / (1 + sin θ) = 1/a

a  =  (1 + sin θ) / cos θ

a2  =  [(1 + sin θ) / cos θ]2

a2  =  [(1 + sin θ)2 / cos2 θ]

a2  =  (1 + sin2θ + 2sin θ)/cos2 θ]

a2 - 1  =  (1 + sin2θ + 2sin θ)/cos2 θ] - 1

a- 1  =  (1 + sin2θ + 2sin θ - cos2 θ)/cos2 θ

a- 1  =  (2 sin2θ + 2sin θ)/cos2 θ

a- 1  = sinθ (sinθ + 1)/cos2θ

a- 1  = sinθ (sinθ + 1)/(1 - sin2θ)

a- 1  = sinθ /(1 - sinθ)  -----(1)

a2 + 1  =  (1 + sin2θ + 2sin θ)/cos2 θ] + 1

 =  (1 + sin2θ + 2sin θ + cos2 θ)/cos2 θ

 =  (1 + 1 + 2sin θ )/cos2 θ

 =  2(1 + sin θ )/(1-sin2 θ)

 =  2/(1-sin θ)  ---(2)

(1)/(2)

(a- 1) / (a+ 1)  =  [sinθ /(1 - sinθ)] / [2/(1-sin θ)]

  =  sinθ

Hnce proved.

After having gone through the stuff given above, we hope that the students would have understood, "Trigonometric Identities Problems with Solutions". 

Apart from the stuff given in this section "Trigonometric Identities Problems with Solutions"if you need any other stuff in math, please use our google custom search here.

HTML Comment Box is loading comments...